Monitoring for a new I3 resistance gene-breaking race of F. oxysporum f. sp. lycopersici (Fusarium wilt) in California processing tomatoes following recent widespread adoption of resistant (F3) cultivars: Challenges with race 3 and 4 differentiation methods - Swett, Cassandra L.; Del Castillo Múnera, Johanna; Hellman, Elizabeth; Helpio, Erin; Gastelum, Megan; Lopez Raymundo, Elver; Johnson, Heather; Oguchi, Rino; Hopkins, Aimee; Beaulieu, Justine; Rodriguez, Fernando (Frontiers in Plant Science, 2023)
Fusarium wilt, caused by F. oxysporum f. sp. lycopersici (Fol), causes losses in tomato production worldwide, with major impacts in California processing tomato. Single gene resistance is the primary management tool, but efficacy has been compromised following the emergence of two successive resistance-breaking races, which in California, emerged within 12 years of resistance deployment. Fol race 3-resistant (F3) processing tomatoes cultivars (containing the I3 resistance gene) were deployed in the state starting ~2009; emergence of a new resistance-breaking race (which would be called race 4) is imminent and early detection will be critical to delay spread while new resistance is sought. Fol race 4 detection is challenged by lack of validated, rapid and accurate diagnostic tools. In evaluating in-planta phenotyping methods, this study found that rapid seedling phenotyping is not reliable and generates false positives for nonpathogens; longer (10 week) mature plant assays are the most reliable but may not be sufficiently timely. As an additional challenge, based on field and greenhouse studies, Fol race 3 can cause symptoms in resistant F3 cultivars at frequencies greater (30%) than expected for off-types (<2%). We developed a three F3 cultivar in-planta assay to overcome the challenges this posed to differentiating Fol race 3 and 4. Using the assay, we determined that all putative resistance-breaking cases were Fol race 3; Fol race 4 was not detected in these early survey efforts. These results highlight needs in developing rapid Fol race 4 detection tools and a better understanding of factors underling inconsistent I3 gene expression to Fol race 3.